THE ARAB SPRING : POPULAR SOCIAL MOVEMENTS OR WESTERN HEGEMONIC RECONSTRUCTION? - Appiah Adou (European Scientific Journal, ESJ, 2015)
Analyses dealing with recent crises in North Africa, the Near and Mideast put forward endegenous factors without hilighting relevent issues. Those conflicts, said to be the expression of poupular aspirations and thirst for democracy and freedom, are more the outcomes a construstruction by the Center confronted with internal contradictions that they try to export in order to adapt the worldwide societal dynamism. Indeed, the advent of new actors, Brazil, Russia, China, and South Africa, ( BRICS), exert a strong pressure on economically advanced countries. This dynamism limits, if not, causes to crumble the hegemony of the Center in southern states. This articles attempts to uncover the real grounds of those social movements in the Arab world by using a different approach of the issue.